(untitled) (Applied Biological Research, 2019)
The present study was envisaged to formulate meat analog nuggets from Oyster mushroom, flaxseed and amaranth and characterize its quality and shelf stability under ambient conditions. The water absorption index, fat absorption index, water activity and total microbial count of meat analog nuggets were analyzed for six months at two months interval. The mean water activity, oil absorption index and microbial count of meat analog nuggets increased from 0.558 to 0.604, 2.60 to 2.75 g g-1 and 0.172 × 104to 2.863 × 104cfu g-1, respectively, during six months storage. However, the water absorption index of meat analog nuggets decreased from 5.06 to 4.03 g g-1 during six months storage. The study revealed higher values of water and oil absorption index in meat analog nuggets formulated from higher levels of freeze-dried Oyster mushroom; while the incorporation of defatted flaxseed decreased water activity of meat analog nuggets. The microbial load of meat analog nuggets was within the permissible limits of BIS (4 × 104 cfu mL-1) throughout storage period of six months.